Governing Children in Street Situations in Pretoria: Vulnerability and Social Protection in South Africa - Matarise, Fungai (University of the Witwatersrand, Johannesburg, 2022)
The vulnerability of children in post-Apartheid South Africa has been a major issue in social and development policy debates for decades now. Children are situated within the wider notion of “Vulnerable Groups” that is a central tenet in South African public and development policy discourse. This thesis examines the vulnerability of children in street situations as defined in the Children’s Act no. 38. of 2005. Children in street situations are a distinct category of vulnerable children that has experienced and continues to experience countless privations on the streets across South Africa. The issue of children in street situations raises fundamental questions about the political, economic and social aspects of inequality, marginality, and social exclusion in the post-Apartheid state. Hence, a central question in debates surrounding the interventions of state agencies on children in street situations is to consider how social and public policy articulate in concrete ways the country’s commitment to social inclusion, social justice and the fight against inequalities. Yet, with specific reference to children in street situations, little is known about the legal, material and practical governance of these category of children in South Africa. This study examines the governance of Children in Street Situations in Pretoria– the administrative capital of South Africa. The Department of Social Development (DSD) is the main provider for social interventions in the country, including in Pretoria. This is an exploratory study, based on my field research with informants at the Department of Social Development (DSD) and related organisations working on addressing the issue of Children in Street Situations. The study combines data from face to-face interviews with social workers at the DSD and telephone conversations with non governmental organisations (NGOs) personnel alongside textual analysis of official documents, policy reports and guidelines, legal provisions and media reports. Using discourse analysis and a post structural deconstructive approach, the thesis examines and unpacks the value and limits of vulnerability as a critical and core concept in understanding social protection in South Africa’s public and development policy. The thesis argues that a critical approach to the conceptualisation of vulnerability in South African public and development policy is important because it frames the legal and institutional responses to categories of people perceived to be in need of social protection, including children in street situations. The thesis develops this argument empirically by analyzing and discussing the representations of children in street situations in South Africa along mostly negative perceptions of these children and underlines how these representations are important to the framing and practice of social protection in aw, legislation and social policy. Furthermore, in discussing some of the social interventions for children in street situations and the challenges involved for DSD workers, this study also finds that the social problem of children in street situations is defined by ambiguity: among social workers at the DSD there are divergent views on whether these children exist and pose a policy challenge or not. Against a generic conceptualisation of children as similarly characterized by vulnerability, the thesis suggests that a further disaggregation of children in street situations as children in a specific social situation is necessary to appreciate their special vulnerabilities and needs. This fits a purposive response, more effective and targeted initiatives in care and protection that enhance their capabilities and well-being of children in street situations.
A thesis submitted in fulfilment of the requirements of the degree of Doctor of Philosophy (Development Studies), to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2022
Keywords: Vulnerability; Governance; Social protection; Social interventions; Children in street situations; Vulnerable Groups; Children’s Act no. 38. of 2005; Department of Social Development (DSD); South Africa; Union Catalogue for Thesis and Dissertation (UCTD); SDG-16: Peace, justice and strong institutions; SDG-11: Sustainable cities and communities